1990
DOI: 10.1099/00207713-40-3-312
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Improved Taxonomy of Xanthomonas

Abstract: Improvement of the taxonomy of the genus Xanthomonas and especially of Xanthomonas campestris, which is subdivided into more than 125 pathovars, is discussed. Recent contributions to the taxonomy of Xanthomonas are reviewed, and on the basis of these data and unpublished data from several laboratories, the usefulness of different phenotypic, chemotaxonomic, and genotypic techniques is discussed. The heterogeneity of several X. campestris pathovars has been demonstrated by sodium dodecyl sulfate electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 27 publications
3
67
0
1
Order By: Relevance
“…vesicatoria. Vauterin et al (49) reported that this pathovar is composed of two unrelated genotypes, which were designated types A and B. These types were later confirmed by protein electrophoresis data (48).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…vesicatoria. Vauterin et al (49) reported that this pathovar is composed of two unrelated genotypes, which were designated types A and B. These types were later confirmed by protein electrophoresis data (48).…”
mentioning
confidence: 67%
“…All of the strains used in this study were selected on the basis of the results of a fingerprint analysis of more than 1,000 Xanthomonas strains in which sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) of proteins was used and on the basis of the results of a FAME analysis, as described previously (48,49,51,52,60). We verified that these organisms were authentic xanthomonads by determining their Xanthomonas-specific protein patterns and fatty acid contents (48,60).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vauterin et al (30) observed that the creation of species solely on the basis of RFLP analysis raises the same objections and poses the same problems for classification and nomenclature as does creating species solely on the basis of pathogenicity for particular plant hosts. It is generally recognized that an orderly nomenclature of plant-pathogenic bacteria will be best served if an accurate overview of the relationships of organisms at the molecular level is obtained and more phenetic data are gathered before individual plantpathogenic species, presently named as pathovars, are reinstated.…”
Section: Molecular Biological Methods In the Taxonomy Of Plant-pathogmentioning
confidence: 99%